Molecular Insight into Dengue Virus Pathogenesis and Its Implications for Disease Control - Diamond, Michael S.; Pierson, Theodore C. (Cell, 2015)
Dengue virus (DENV) is a mosquito-transmitted RNA virus that infects an estimated 390 million humans each year. Here, we review recent advances in our understanding of the biology of DENV and describe knowledge gaps that have impacted the development of effective vaccines and therapeutics. Dengue virus infects nearly 400 million humans each year. Recent insights into the disease have driven the development of vaccines and therapeutics.